Sustaining Wheat Productivity and Maintaining Soil Fertility in Maize-Wheat System - Tripathi, Bhaba P; Tuladhar, Junu K (Nepal Agriculture Research Journal, 2011)
Field experiments on maize-wheat system were carried out in rainfed upland (bari) at Agricultural Research Station, Lumle for three years (1994/95-1996/97) to determine the effect of different quality organic materials on maize and wheat yields and soil properties. Wheat grain yield significantly differed over years and the highest mean grain yield (1.98 t ha-1) was recorded in the treatment of mixture of low and high quality organic materials (maize + leaf litter, farmyard manure). Maize and wheat grain as well as straw yield significantly differed over years. In all the three years, the mixture of low and high quality organic materials produced the highest grain yield of maize plus wheat ranging from 6.72 to 2.20 t ha-1 with mean yield of 4.43 t ha-1. Mean N uptake by wheat grain and straw ranged from 32.2 to 40.4 kg ha-1 and 13.8 to 16.0 kg ha-1, respectively in different treatments. Similarly, mean P uptake by wheat grain was the highest (25.4 kg ha-1) in the mixture treatment while mean P uptake by wheat straw was the highest (26.5 kg ha-1) in low quality organic materials. Mean soil pH after wheat harvest was the lowest (5.1) in the low quality organic material. Organic carbon and available P ranged from 3.4 to 3.7% and from 329 to 370 ppm, respectively in different treatments while total N and exchangeable K increased to 0.31% and 0.2 me/100g, respectively with the application of low quality organic material. The three years result showed that semi-decomposed organic materials were more efficient in improving and stabilizing production of wheat and maize yields in maize-wheat system as well as in maintaining N fertility than high quality organic materials. Key words: Maize-wheat system; Organic materials; Soil fertility; Sustainability DOI: http://dx.doi.org/10.3126/narj.v4i0.4861 Nepal Agriculture Research Journal Vol. 4&5, 2001/2002 Page: 31-36 Uploaded date: 8 June, 2011